1997
DOI: 10.1074/jbc.272.33.20364
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Carbonic Anhydrase Variants Displayed on Phage

Abstract: In all metalloenzymes, hydrophobic residues surround the metal binding site. In carbonic anhydrase II (CAII) residues Phe 93 , Phe 95 , and Trp 97 flank two of the three histidines that coordinate zinc to form a hydrophobic cluster beneath the zinc binding site. A library of CAII variants differing in these hydrophobic amino acids was prepared using cassette mutagenesis, then displayed on filamentous phage, and screened for proteins retaining high zinc affinity. Wild-type CAII was enriched 20-fold by selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 63 publications
3
41
0
Order By: Relevance
“…If these observed rates of CadC-metal encounter complex formation reflect true bimolecular rate constants, they are equal to, or orders of magnitude larger, than those reported for other metalloproteins, including Bacillus cereus b-lactamase (10 7 M À1 s À1 for Zn(II)) [45], Zn(II) E9 endonuclease (10 6 M À1 s À1 ) [28], Mn(II) FosA (3 · 10 5 M À1 s À1 ) [27], Bi(III)-transferrin (2 · 10 5 M À1 s À1 ) [46], Zn(II) carbonic anhydrase (10 5 M À1 s À1 ) [47] and Cu(II)-azurin (2.2 · 10 3 M À1 s À1 ) [37]. Although rapid, k obs1 for Pb(II)-CadC complex is slower than association rate constant for the binding of Zn(II) to reduced glutathione [48].…”
Section: The Role Of Kinetics In Metal Regulationmentioning
confidence: 99%
“…If these observed rates of CadC-metal encounter complex formation reflect true bimolecular rate constants, they are equal to, or orders of magnitude larger, than those reported for other metalloproteins, including Bacillus cereus b-lactamase (10 7 M À1 s À1 for Zn(II)) [45], Zn(II) E9 endonuclease (10 6 M À1 s À1 ) [28], Mn(II) FosA (3 · 10 5 M À1 s À1 ) [27], Bi(III)-transferrin (2 · 10 5 M À1 s À1 ) [46], Zn(II) carbonic anhydrase (10 5 M À1 s À1 ) [47] and Cu(II)-azurin (2.2 · 10 3 M À1 s À1 ) [37]. Although rapid, k obs1 for Pb(II)-CadC complex is slower than association rate constant for the binding of Zn(II) to reduced glutathione [48].…”
Section: The Role Of Kinetics In Metal Regulationmentioning
confidence: 99%
“…187 Fierke and co-workers conducted a series of studies in which they measured the affinities of different metals to HCA II and its active site mutants to determine the basis of selectivity for zinc in this protein. 251,311,321,322 The investigators looked at the influence of hydrophobic core residues Phe93, Phe95, and Trp97 on binding of metals and found that substitution of those residues with smaller side chains reduced the affinity of the protein to Zn II and Co II but increased the affinity to Cu II . 311,321 X-ray analysis of the mutants revealed new cavities formed in the core of the protein and shifts in the positions of metal-coordinating His94 and secondshell ligand Gln92.…”
Section: Metalloenzyme Variantsmentioning
confidence: 99%
“…251,311,321,322 The investigators looked at the influence of hydrophobic core residues Phe93, Phe95, and Trp97 on binding of metals and found that substitution of those residues with smaller side chains reduced the affinity of the protein to Zn II and Co II but increased the affinity to Cu II . 311,321 X-ray analysis of the mutants revealed new cavities formed in the core of the protein and shifts in the positions of metal-coordinating His94 and secondshell ligand Gln92. 251 The investigators concluded that the aromatic residues, although they do not directly coordinate the metal, preorient the metal-binding side chains in such a fashion as to favor tetrahedral zinc-binding geometry and to destabilize alternative geometries.…”
Section: Metalloenzyme Variantsmentioning
confidence: 99%
“…Ϫ1 at pH 7.0, 30°C) (20). Noteworthy, incubation of 40 M wild type Hsp33 in 2 mM TPEN showed that the apparent half-time of zinc release was only 160 Ϯ 10 min at 23°C.…”
mentioning
confidence: 99%